Lysophosphatidic Acid Is Associated With Cardiac Dysfunction and Hypertrophy by Suppressing Autophagy via the LPA3/AKT/mTOR Pathway - Yang, Jinjing; Xu, Jiyao; Han, Xuebin; Wang, Hao; Zhang, Yuean; Dong, Jin; Deng, Yongzhi; Wang, Jingping (Frontiers in Physiology, 2018)
Background: Lysophosphatidic acid (LPA), as a phospholipid signal molecule, participates in the regulation of various biological functions. Our previous study demonstrated that LPA induces cardiomyocyte hypertrophy in vitro; however, the functional role of LPA in the post-infarct heart remains unknown. Growing evidence has demonstrated that autophagy is involved in regulation of cardiac hypertrophy. The aim of the current work was to investigate the effects of LPA on cardiac function and hypertrophy during myocardial infarction (MI) and determine the regulatory role of autophagy in LPA-induced cardiomyocyte hypertrophy. Methods: In vivo experiments were conducted in Sprague-Dawley rats subjected to MI surgery or a sham operation, and rats with MI were assigned to receive an intraperitoneal injection of LPA (1 mg/kg) or vehicle for 5 weeks. The in vitro experiments were conducted in H9C2 cardiomyocytes. Results: LPA treatment aggravated cardiac dysfunction, increased cardiac hypertrophy, and reduced autophagy after MI in vivo. LPA suppressed autophagy activation, as indicated by a decreased LC3II-to-LC3I ratio, increased p62 expression, and reduced autophagosome formation in vitro. Rapamycin, an autophagy enhancer, attenuated LPA-induced autophagy inhibition and cardiomyocyte hypertrophy, while autophagy inhibition with Beclin1 siRNA did not further enhance the hypertrophic response in LPA-treated cardiomyocytes. Moreover, we demonstrated that LPA suppressed autophagy through the AKT/mTOR signaling pathway because mTOR and PI3K inhibitors significantly prevented LPA-induced mTOR phosphorylation and autophagy inhibition. In addition, we found that knockdown of LPA3 alleviated LPA-mediated autophagy suppression in H9C2 cardiomyocytes, suggesting that LPA suppresses autophagy through activation of the LPA3 and AKT/mTOR pathways. Conclusions: These findings suggest that LPA plays an important role in mediating cardiac dysfunction and hypertrophy after a MI, and that LPA suppresses autophagy through activation of the LPA3 and AKT/mTOR pathways to induce cardiomyocyte hypertrophy.